The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1467-9922.2009.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Demands of Television Programs

Abstract: This study investigated vocabulary coverage and the number of encounters of lowfrequency vocabulary in television programs. Eighty-eight television programs consisting of 264,384 running words were categorized according to genre. Television shows were classified as either British or American and then put into the following genres: news, drama, situation comedy, older programs, children's programs, and science fiction. The results showed that knowledge of the most frequent 3,000 word families plus proper nouns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
265
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 296 publications
(296 citation statements)
references
References 37 publications
20
265
2
4
Order By: Relevance
“…They suggested that for learners with the appropriate vocabulary size, increased viewing should lead to increased vocabulary learning because research on incidental vocabulary learning has shown that the more unknown words are encountered in context, the more likely they are to be learned (Horst, Cobb, & Meara, 1998;Jenkins, Stein, & Wysocki, 1984;Rott, 1999;Saragi, Nation, & Meister, 1978;Waring & Takaki, 2003;Webb, 2007). Webb and Rodgers (2009a) findings also shed light on differences between television genres. Children's programs were found to have the smallest vocabulary load; the most frequent 2000 word families, plus proper nouns and marginal words accounted for 95% coverage.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…They suggested that for learners with the appropriate vocabulary size, increased viewing should lead to increased vocabulary learning because research on incidental vocabulary learning has shown that the more unknown words are encountered in context, the more likely they are to be learned (Horst, Cobb, & Meara, 1998;Jenkins, Stein, & Wysocki, 1984;Rott, 1999;Saragi, Nation, & Meister, 1978;Waring & Takaki, 2003;Webb, 2007). Webb and Rodgers (2009a) findings also shed light on differences between television genres. Children's programs were found to have the smallest vocabulary load; the most frequent 2000 word families, plus proper nouns and marginal words accounted for 95% coverage.…”
Section: Introductionmentioning
confidence: 97%
“…In a corpus-driven study looking at the number of words needed to understand the vocabulary in television programs, Webb and Rodgers (2009a) found that a vocabulary size of 3000 word families plus proper nouns and marginal words provided 95.45% coverage of a corpus made up of 88 television programs from a variety of genres. They reported that knowing the most frequent 3000 word families may be sufficient for adequate comprehension of television programs and that a learning approach which involved regular viewing could lead to large incidental vocabulary learning gains.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Nation (2006) proposed that 98 % coverage of vocabulary is "ideal" for vocabulary comprehension of television programs. Then, Webb and Rodgers (2009) investigated the vocabulary demands of American television programs such as news, drama, science fiction, children's programs, older programs, and situation comedies and found that American drama reached 95% coverage of 3,000 most frequent word families and 98% coverage of 6,000 word families compared to American news' 95% coverage of 4,000 word families and 98% coverage of 8,000 word families and children's program's 95% coverage of 2,000 word families and 98% of 5,000 word families. According to their results, we might hypothesize that the vocabulary level of American drama seems to be higher than American children's programs and lower than American news.…”
Section: The Level Of Vocabulary In Tv Drama Is Appropriate For Mementioning
confidence: 99%
“…Studies of lexical coverage have indicated the importance of vocabulary for comprehension of both written and spoken input (Schmitt, Jiang & Grabe 2011;van Zeeland & Schmitt 2013a), as well as the vocabulary sizes that may indicate comprehension of different discourse types (Meara 1991(Meara , 1993Hirsh & Nation 1992;Adolphs & Schmitt 2003;Nation 2006;Webb & Rodgers 2009a, 2009b. Despite the interest that this line of research has generated, Liu & Nation's (1985) study remains the only one that has looked at how lexical coverage affects guessing from context.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have in turn contributed to greater focus in the research literature on the number of words necessary to reach the lexical coverage points associated with comprehension of spoken discourse (e.g. Nation 2006;Webb & Rodgers 2009a, 2009bRodgers & Webb 2011) and written (Hirsh & Nation 1992;Adolphs & Schmitt 2003;Nation 2006;Webb & Macalister 2013), as well as the potential to incidentally learn vocabulary through comprehensible input (Webb 2010). Liu & Nation's (1985) study indicated that lexical coverage affects the potential to successfully guess words from context; there is a better chance of successfully inferring unknown words in texts with a higher lexical coverage than passages with a lower lexical coverage.…”
Section: Introductionmentioning
confidence: 99%